Compreensão de professores de instituição especializada sobre leitura e escrita de alunos com deficiência intelectual - Buzetti, Miryan Cristina (2015)
The objective of this study is to analyze the understanding that teachers serving students with intellectual disabilities in a specialized institution have on the teaching of reading and writing. National theses and dissertations of studies have shown that teaching reading and writing is possible for people with intellectual disabilities based on different theoretical perspectives. The research is qualitative / quantitative exploratory type, the instrument used was a semi-structured interview. It was conducted in four APAEs located in the state of São Paulo, being interviewed a total of 11 teachers who worked with the teaching of students with intellectual disabilities for more than three years. The categories of analysis of the interviews were defined from the content analysis proposed by Bardin. In the data analysis it observed aspects such difficulty by the teacher to define intellectual disability and teaching and learning theoretical confusion - Methodological about the process of reading and writing learning and mostly practices decontextualized teaching and without reflection. The study points out the need to review teacher training, updating and further clarification on this matter and the need for greater interaction between researchers and professionals, thus enabling the socialization practices.